The portrait is me: On the exhibition “Intervened Portraits” by Rogelio Cuéllar (REVISTA NODO, 2025)
Introductory remarks to the exhibition “Intervened Portraits”, by Mexican photographer Rogelio Cuellar, which was presented at the University Book House (Casul) of the UNAM, Mexico City, from September 6 to October 10, 2025.
Keywords: Photography; Art